Improvement Performans of Pregnant Cross Awassi Sheep using Silage Total Mixed Ration (Tmr) Feed Technology - Aisah, Intan Nur; Daning, Dewi Ratih Ayu; Wijoyo, Iman Aji (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
The effect of feeding Pakchong and Indigofera-based silage Total Mixed Ration (TMR) on the production performance of pregnant Cross Awassi sheep was evaluated using 6 pregnant sheep, which were randomly divided into two treatment groups. Three sheep were allocated to the control group (P0) which was fed a conventional diet based on fresh forage and standard concentrate, while the other three were placed in the treatment group (P1) which was fed fermented silage TMR for 14 days. Each sheep received feed at 3.5% of body weight per day, with access to drinking water ad libitum. During the 30-day study, feed consumption, daily body weight gain (ADG), feed conversion (FCR), and cempe birth weight were analyzed. The results showed that feed consumption in the treatment group (10.62±1.192 kg/head/day) was higher than the control group (9.84±1.056 kg/head/day). ADG of the treatment group (1.2±0.10 kg) was higher than the control group (0.85±0.12 kg). Birth weight of cempe in the treatment group (4.08±0.769 kg) was higher than the control group (3.72±0.685 kg) with a statistically significant difference (P < 0.05). The FCR value was lower in the treatment group (14.93) than the control group (20.24), indicating better feed efficiency. Therefore, feeding Pakchong and Indigofera-based TMR silage can improve feed efficiency, productivity, and cempe birth weight in pregnant Cross Awassi Sheep.